The Influence of Cigarette Advertising Exposure on Teenage Smoking Cessation Intention - Sujono Riyadi; Marm Marm (Indonesian Journal of Global Health Research, 2025)
Smoking is one of the serious health problems among adolescents in Indonesia, and exposure to cigarette advertisements can influence their intention to quit smoking. This study aims to analyze the effect of exposure to cigarette advertisements on adolescents' intention to quit smoking in Sumenep, Madura.Methods: This study used a quantitative design with a cross-sectional approach. A total of 200 adolescents aged 13 to 18 years in Sumenep were selected as respondents using purposive sampling. Data were collected through questionnaires measuring exposure to cigarette advertisements and the intention to quit smoking. Data analysis was conducted using Pearson correlation tests.Results: The analysis showed a significant negative relationship between exposure to cigarette advertisements and adolescents' intention to quit smoking, with a Pearson correlation value of r = -0.157 and p = 0.027. The majority of respondents were male (70%) and had a high school education (76.5%).Conclusion: This study shows that the higher the adolescents' exposure to cigarette advertisements, the lower their intention to quit smoking. These findings highlight the importance of stricter regulations on cigarette advertisements in media accessed by adolescents, as well as the need for more effective educational programs to encourage adolescents in their efforts to quit smoking.